2021
DOI: 10.1101/2021.11.03.467145
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A phosphoinositide and RAB switch controls early macropinocytosis

Abstract: Macropinocytosis is a non-selective endocytic process by which cells take up large amounts of extracellular fluids into giant vesicles known as macropinosomes. This mechanism is used by immune cells to sample the surroundings for antigens and can be exploited by cancer cells for nutrient uptake. What determines the fate of macropinosomes after they have been internalized is largely unknown. Here we investigate the role of the phosphatidylinositol 3-kinase VPS34/PIK3C3 and its product phosphatidylinositol 3-pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 68 publications
(93 reference statements)
0
3
0
Order By: Relevance
“…Although morphologically comparable to canonical macropinosomes, the similarity in composition and formation of IAMs to "classical" macropinosomes has remained unclear. A recent study (Spangenberg et al 2021) found macropinosome maturation to be VPS34-dependent with inhibition of VPS34 leading to the refusion of macropinosomes with the plasma membrane, via RAB10 and RAB11A recruitment. Here, our results contrasted with those of Spangenberg et al with the VPS34mediated PI(3)P+/SNX8+ IAMs subset maturing to RAB11A, highlighting how these pathogen-controlled compartments differ from canonical macropinosomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although morphologically comparable to canonical macropinosomes, the similarity in composition and formation of IAMs to "classical" macropinosomes has remained unclear. A recent study (Spangenberg et al 2021) found macropinosome maturation to be VPS34-dependent with inhibition of VPS34 leading to the refusion of macropinosomes with the plasma membrane, via RAB10 and RAB11A recruitment. Here, our results contrasted with those of Spangenberg et al with the VPS34mediated PI(3)P+/SNX8+ IAMs subset maturing to RAB11A, highlighting how these pathogen-controlled compartments differ from canonical macropinosomes.…”
Section: Discussionmentioning
confidence: 99%
“…We remarked however that SNX8 recruitment to the BCV remained, implying a PI(3)-kinase independent recruitment to the bacterial compartment. Given the PI(3)P-dependent recruitment of SNX8 together with RAB5A, we reasoned that the RAB5 effector class III PI(3)P kinase VPS34 (Vacuolar Sorting Protein 34) was involved as it has a reported role in early endosome and macropinosome PI(3)P maturation (Bohdanowicz et al 2013, Spangenberg et al 2021). To test this hypothesis, we used the VPS34-specific inhibitor (SAR405) has been described to impair VPS34 function in canonical macropinosomes (Ronan et al 2014, Spangenberg et al 2021).…”
Section: Snx8/pi(3)p Impairment To Iams Hampered Shigella Bcv Egressmentioning
confidence: 99%
See 1 more Smart Citation